Contribuições das práticas da terapia ocupacional nos centro de atenção psicossocial álcool e drogas: uma revisão da literatura - Wellichan, Thaina Lorena (Universidade Federal de São Carlos, 2024)
Chemical dependence is recognized by the World Health Organization Health (WHO) as a disease of a climatic and progressive nature, worsening over the years time and being triggered most of the time by social factors, that is, poverty, social inequality and other contemporary problems, making not only a issue of physical and mental health. The role of the occupational therapist within a The Psychosocial Care Center for Alcohol and other Drugs (CAPs AD) is essential and should always have the user as the main point, turning your attention to them and their singularities, since from a therapeutic plan and through doing (act, actions, activities), the patient regulates himself as a subject who creates, acts, regulates, organizes and manages his daily life with serious activities for you. Objective: to map operations and practices training by occupational therapists within the scope of CAPs AD, or other health equipment, carrying out a bibliographical survey to be analyzed. Methodology: systematic review, which consists of a bibliographic review of the literature based on a systematic review on the work of occupational therapists in Care Centers Psychosocial Alcohol and Drugs regardless of the year, in order to observe what changes these practices suffered over the years Analysis of results: based on bibliographical search and application of thematic analysis, contributed significantly to the development new research, reinforcing the importance of publishing research and reports of experiences of these practices, since all documentation may influence the practices of other professionals in different locations and even allow an exchange of knowledge between them, in addition to having an informative function for society, they begin to explain which activities are carried out and how a Psychosocial Care Center for Alcohol and Drugs.
Contributions of occupational therapy practices in alcohol and drug psychosocial care centers: a literature review
Keywords: Saúde mental; Drogas; Mental health; Psychoactive substance; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA